Cassava processing among smallholder farmers in Cameroon: opportunities and challenges - Njukwe, E.; Onadipe, O.; Amadou Thierno, D.; Hanna, R.; Kirscht, H.; Maziya-Dixon, B.B.; Araki, S.; Ngue-Bissa, T. (2014)
The study was conducted in three regions (Southwest and Littoral, South and Centre, West and Northwest) of Cameroon to document cassava processed products andtoassess processing constraints among small-holder farmers. A total of twelve small-scale processing units and five marketer groups with six fabricators were contacted and interviewed. In addition, two operational and two non-operational medium-scale processing factories was visited.Key informant interviews and focused group discussions wasconducted to collect information on their activities. Results indicate that 68.75% of women and 31.25% of men are involved in cassava processing and marketing activities with Bamenda recording (100%) in gari processing and Ebolowa (100%) in baton processing. The percentage score for all products is in the order; fufu (95.00%), chips (86.25%), gari (72.50%), baton (62.50%) and flour (18.75%) with cassava flour having the least score in the entire antenna; Ebolowa (10.71%), Douala (20:00%) and Bamenda (25.93%). Apart from baton (steamed fermented cassava paste wrapped and tied in leaves) that was reported processed among groups, other products were processedat individual and household levels. The profit margins of these processed products are small due to poor quality products, although labourinvestments are high compared with those of medium and large-scale processing factories. Market linkage needs strengthening among the stakeholders and national sensitization on cassava processing could helpcreate awareness and get the attention of the government for policy drive.